Advances in Manufacturing Processes Select Proceedings of ICEMMM 2018 - Vijay Sekar, K. S.; Gupta, Manoj; Arockiarajan, A.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book comprises selected proceedings of the International Conference on Engineering Materials, Metallurgy and Manufacturing (ICEMMM 2018). It discusses innovative manufacturing processes, such as rapid prototyping, nontraditional machining, advanced computer numerical control (CNC) machining, and advanced metal forming. The book particularly focuses on finite element simulation and optimization, which aid in reducing experimental costs and time. This book is a valuable resource for students, researchers, and professionals alike.
1. Modelling, analysis and simulation of manufacturing processes -- 2. Materials forming and machining -- 3. Welding and joining processes -- 4. Mechanical behavior and fracture -- 5. Tooling, testing and evaluation of machining -- 6. High-speed/precision machining -- 7. Laser processing -- 8. Casting -- 9. Non-traditional machining.
Keywords: Manufactures; Coatings; Tribology; Corrosion and anti-corrosives.; Materials; Lasers; Machines, Tools, Processes; Coatings; Tribology; Corrosion; Materials Engineering; Laser